2020
DOI: 10.1038/s41598-020-72103-6
|View full text |Cite
|
Sign up to set email alerts
|

Long-term changes in habitat and trophic level of Southern Ocean squid in relation to environmental conditions

Abstract: Long-term studies of pelagic nekton in the Southern Ocean and their responses to ongoing environmental change are rare. Using stable isotope ratios measured in squid beaks recovered from diet samples of wandering albatrosses Diomedea exulans, we assessed decadal variation (from 1976 to 2016) in the habitat (δ13C) and trophic level (δ15N) of five important Southern Ocean squid species in relation to indices of environmental conditions—Southern Oscillation Index (SOI) and Southern Annular Mode (SAM). Based on δ1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 72 publications
0
13
0
Order By: Relevance
“…Changes in small and largescale ocean dynamics will affect cross-frontal exchange and the dispersal of plankton. Such changes in the rates of mixing between polar, sub-polar and subtropical waters may also potentially disrupt the life cycles of fish and cephalopod species that cross oceanic fronts during development, thus affecting their role in Southern Ocean food webs (Murphy et al, 2007;McMahon et al, 2019;Saunders et al, 2019;Abreu et al, 2020). The APF is not expected to undergo major changes in location in the coming century (Meijers et al, 2019b), potentially limiting the southward extension of the distributions in the Southern Ocean of pelagic fish species from farther north (Boyce et al, 2008).…”
Section: Why Southern Ocean Ecosystems Matter and Why They Are A Priority For The Futurementioning
confidence: 99%
“…Changes in small and largescale ocean dynamics will affect cross-frontal exchange and the dispersal of plankton. Such changes in the rates of mixing between polar, sub-polar and subtropical waters may also potentially disrupt the life cycles of fish and cephalopod species that cross oceanic fronts during development, thus affecting their role in Southern Ocean food webs (Murphy et al, 2007;McMahon et al, 2019;Saunders et al, 2019;Abreu et al, 2020). The APF is not expected to undergo major changes in location in the coming century (Meijers et al, 2019b), potentially limiting the southward extension of the distributions in the Southern Ocean of pelagic fish species from farther north (Boyce et al, 2008).…”
Section: Why Southern Ocean Ecosystems Matter and Why They Are A Priority For The Futurementioning
confidence: 99%
“…Antarctic squid are likely to be influenced by climate change, including by changes in mesoscale oceanography, position of the oceanic fronts (and associated productivity), sea ice extent, and ocean acidification (Rodhouse, 2013;Xavier et al, 2018). A recent long-term study showed that the habitat of Taonius notalia, Gonatus antarcticus, G. glacialis, and Histioteuthis atlantica had changed over the last 50 years despite their trophic levels remaining similar (Abreu et al, 2020).…”
Section: Squidmentioning
confidence: 99%
“…The study of apex predators' trophic ecology can reveal a great deal of information due to the importance of predator-prey relationships and their dynamics on the evolution and structure of animal communities (Forero et al 2004). Apex predators such as cetaceans, seabirds and large predatory fish constitute an ideal model for studying trophic relationships, as they tend to integrate long-term and large-scale ecosystem signals due to their high position in food webs (Einoder 2009;Abreu et al 2020). Each component (i.e.…”
Section: Introductionmentioning
confidence: 99%